Advanced financial risk management : tools and techniques for integrated credit risk and interest rate risk management - Deventer, Donald R. van, 1951-; Imai, Kenji, 1963-; Mesler, Mark (Wiley, 2013)
"Practical tools and advice for managing financial risk, updated for a post-crisis world Advanced Financial Risk Management bridges the gap between the idealized assumptions used for risk valuation and the realities that must be reflected in management actions. It explains, in detailed yet easy-to-understand terms, the analytics of these issues from A to Z, and lays out a comprehensive strategy for risk management measurement, objectives, and hedging techniques that apply to all types of institutions."--Resumé vydavatele
Keywords: finanční rizika; kreditní riziko; rizikový management; financial risks; credit risk; risk management; elektronické knihy; electronic books